Integrated management of groundwater quantity, physicochemical properties, and microbial quality in West Nile delta using a new MATLAB code and geographic information system mapping - Mohamed Shehata; Samir M. Zaid; Soha T. Al-Goul; Ashwag Shami; Khalid M. Al Syaad; Ahmed Ezzat Ahmed; Yasser S. Mostafa; Diana A. Al-Quwaie; Mada F. Ashkan; Fatimah S. Alqahtani; Yusuf A. Hassan; Taha F. Taha; et al. (Scientific Reports, 2024)
Abstract Groundwater is an excellent alternative to freshwater for drinking, irrigation, and developing arid regions. Agricultural, commercial, industrial, residential, and municipal activities may affect groundwater quantity and quality. Therefore, we aimed to use advanced methods/techniques to monitor the piezometric levels and collect groundwater samples to test their physicochemical and biological characteristics. Our results using software programs showed two main types of groundwater: the most prevalent was the Na–Cl type, which accounts for 94% of the groundwater samples, whereas the Mg–Cl type was found in 6% of samples only. In general, the hydraulic gradient values, ranging from medium to low, could be attributed to the slow movement of groundwater. Salinity distribution in groundwater maps varied between 238 and 1350 mg L−1. Although lower salinity values were observed in northwestern wells, higher values were recorded in southern ones. The collected seventeen water samples exhibited brackish characteristics and were subjected to microbial growth monitoring. Sample WD12 had the lowest total bacterial count (TBC) of 4.8 ± 0.9 colony forming unit (CFU mg L−1), while WD14 had the highest TBC (7.5 ± 0.5 CFU mg L−1). None of the tested water samples, however, contained pathogenic microorganisms. In conclusion, the current simulation models for groundwater drawdown of the Quaternary aquifer system predict a considerable drawdown of water levels over the next 10, 20, and 30 years with the continuous development of the region.